The feeling of loneliness in persons of the third age: causes and factors - Veronica DIWO; Nicolae SILISTRARU (Acta et Commentationes, Sciences of Education, 2025)
In this article, we describe the phenomenon of aging as a universal and inevitable process, and its awareness constitutes a fundamental dimension of the human experience. Loneliness in old age is not just a lack of social contacts, but a subjective experience of disconnection and meaninglessness. Even people living in communities or families can feel lonely if they do not feel valued, listened to or involved in authentic emotional relationships. Studies show that loneliness in the elderly is not only an emotional discomfort, but also has direct effects on physical and mental health, increasing the risk of depression, dementia and cardiovascular disease. In general, numerous studies demonstrate that age-related stereotypes and the marginalization of older people lead to negative psychological effects – from decreased self-esteem to social isolation and depression. Therefore, aging is not reduced to biological processes, but is significantly shaped by the way society perceives and treats the elderly.